1989
DOI: 10.1029/jd094id11p13213
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lightning type and convective state of thunderclouds

Abstract: Thunderstorm case studies and earlier observations are described which illuminate the relationship between cloud vertical development and the prevalence of intracloud (IC) and cloud-to-ground (CG) lightning. A consistent temporal evolution starting with peak IC activity changing to predominant CG activity and concluding with strong outflow (microburst) suggests that ice is responsible for both the electrical (i.e., lightning) and dynamical (i.e., microburst) phenomena. The IC activity is attributed to the updr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
147
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(174 citation statements)
references
References 23 publications
22
147
0
5
Order By: Relevance
“…However, some studies showed that IC preceded CG in thunderstorm activity (Williams et al 1989). Thus, time lag between maximum PWV and total lightning activity including IC and CG might be shorter than that between maximum PWV and CG analyzed in this study.…”
Section: Water Vapor Variation Associated With Individual Thunderstormmentioning
confidence: 73%
“…However, some studies showed that IC preceded CG in thunderstorm activity (Williams et al 1989). Thus, time lag between maximum PWV and total lightning activity including IC and CG might be shorter than that between maximum PWV and CG analyzed in this study.…”
Section: Water Vapor Variation Associated With Individual Thunderstormmentioning
confidence: 73%
“…It deliberately excludes cloud-to-cloud flashes since they are irrelevant for the main purpose of the network: detection of strikes leading to damage and the evaluation of lightning risk. This is disadvantageous for meteorological sciences since the main share of all flashes are cloud-to-cloud flashes and the flash activity of a thunderstorm cell often starts with cloud-to-cloud flashes (Williams et al, 1989).…”
Section: Lightning-detection Network and Datamentioning
confidence: 99%
“…Another major user of lightning data is the hydro utilities, where lightning strikes can cause havoc with the distribution of electrical power. Recent case studies have shown that lightning is related to other severe weather hazards -downbursts, tornadoes, heavy rains (Williams et al, 1989;Kane, 1991;Keighton et al, 1991). The lightning flash density for slow-moving high-rainfall storms has been related to heavy rain events (Clodman and Chisholm, 1994a).…”
Section: Tornado Incidencementioning
confidence: 99%
“…Since there are few Doppler radars across the country at this time, this study attempted to verify a three-dimensional reflectivity algorithm for the occurrence of downbursts (Stewart, 1991) with Doppler observations. d Lightning Lightning is a complex electrical phenomenon and is very difficult to forecast, partly because it is not fully understood (Uman, 1987;Williams et al, 1989). Forecasts for the Canadian forestry program have focussed on the expected fire damage in relation to ground lightning counts.…”
Section: Tornado Incidencementioning
confidence: 99%